Mid-Day Meal Scheme in India: Current status, Critical Issues and Challenges - Hoque, MD Asraul (International Journal of Education, Language, and Social Science, 2023)
This piece of work examines the impact of the midday meal program on body mass index using secondary data on several Indian states. India has implemented the Mid-day Meal Program to improve the enrollment, attendance, retention, and academic success of school-aged children. A significant portion of schoolchildren from lower socioeconomic categories rely on cooked midday meals. When it comes to the pattern of midday meal consumption, girls outnumber boys among those who never ate it and those who stopped eating it, but when it comes to those who maintained eating it, boys outnumber girls. Less youngsters who take use of the midday meal the higher their academic grades are. The majority of kids are underweight (have a low body mass index), and boys make up a larger percentage of the underweight kids than girls do. When compared to children who are Above Poverty Line (BPL), a greater percentage of youngsters who fall into the Below Poverty Line (BPL) group have low body mass indices. To meet the goals of the Mid-day Meal Scheme, it is important to avoid repetition of the roughly same sort of meal menu.